Mexican Americans in a Dallas Barrio - Achor, Shirley (University of Arizona Press, 1978)
Vividly describes the beauty and pain of day-to-day barrio life in Dallas. Achor's portrayal of the residents challenges long-accepted stereotypes of traditional Mexican American culture and Southwestern barrio life.